Reconstructing Stakeholder Trust in an Existential Crisis: A Conceptual Study of PT Sritex's Crisis Communication Management Post-Bankruptcy Decision - Nadia Pipit Safitri; Alfia Risma Kinanti; Julia Ari Safira; Pramudya Ibnu Subrata (CITACONOMIA, 2026)
The global textile industry faced significant structural upheavals in the 2024–2025 period, placing strategic entities like PT Sri Rejeki Isman Tbk (Sritex) under extreme existential threats. This conceptual article examines the anomaly of corporate resilience where a formal bankruptcy status is met with massive social and political support rather than reputational collapse. Using a qualitative-descriptive approach, the study synthesizes Situational Crisis Communication Theory (SCCT) and Image Repair Theory with the realities of economic nationalism in developing economies. The analysis reveals that the integration of a